2016
DOI: 10.1007/s00380-016-0809-y
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of oral nicorandil on contrast-induced nephropathy in patients with renal insufficiency undergoing elective cardiac catheterization

Abstract: This study aims to investigate the preventive effect of oral nicorandil on contrast-induced nephropathy (CIN) in patients with renal insufficiency undergoing elective cardiac catheterization. A total of 240 patients with an estimated glomerular filtration rate (eGFR) of 60 mL/min or less, who were undergoing elective cardiac catheterization, were randomly assigned to nicorandil group (n = 120, 10 mg nicorandil, three times daily from 2 days before to 3 days after procedure) or control group (n = 120, matching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…The remaining 8 RCTs underwent full‐text review and 4 were further excluded because three of them were repeated abstracts of already included RCTs, and the other one was not with the treatment arm of nicorandil. Finally, four RCTs were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 8 RCTs underwent full‐text review and 4 were further excluded because three of them were repeated abstracts of already included RCTs, and the other one was not with the treatment arm of nicorandil. Finally, four RCTs were included.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, four RCTs including 709 patients with renal dysfunction or at risk for CIN, who were scheduled for coronary angiography (CAG) or percutaneous coronary intervention (PCI), were included . All of the RCTs were performed in Asian countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4B). Table 1 Study population and nicorandil administration of included studies Ko et al 5 Nawa et al 10 Fan et al 11 Iranirad et al 12 Study Change in cystatin C Pooled analysis of percentage change in cystatin C from baseline showed that, compared with control, nicorandil was associated with a non-significant trend towards decreased cystatin C (WMD = −2.18%, 95% CI: −4.39 to 0.02) ( Fig. 5A).…”
Section: Changes In Scrmentioning
confidence: 99%